Simulation of material fracture in solids and structures using ANSYS - Ong, Yong Ming (2016)
Bolted connection is a commercially recognized prime joining system for assembling cold formed structural steel sheet members. An understanding of the failure types is important in the successful design of a bolted connection. Net-section failure is amongst the most catastrophic and is attributed fundamentally to stress concentrations induced by the presence of bolt holes. While the Virtual Crack Extension (VCE) approach has been adopted traditionally by researchers to predict crack propagation emanating from bolt hole(s), it is inherently limited by the need to hypothetically introduce a pre-notch near the bolt hole to simulate crack initiation and remesh the crack extended model with a new set of mesh profile. Hence, the present study seeks to establish an alternative approach, known as the element death approach, to predict crack propagation within the net-section of a finite-width flat steel sheet with a central circular hole subjected to uniaxial tension. Two cases of possible propagation namely single crack on one side of the hole as well as two symmetric cracks on both sides of the hole are studied. The studies are carried out for three diameter-to-width ratios d/W=0.1625, 0.4125 and 0.7625. The element death approach is based on the assumption that failure occurs if the ANSYS-determined von Mises strain of any elements has exceeded the ‘fracture strain’, i.e., the strain at maximum elongation. Failed elements are unselected thereby rendering zero stiffness. Remeshing, loading and unselecting of failed elements are repeated until the crack propagates to the entire width of the sheet. The residual strength of the sheet at different crack lengths calculated by the element death approach are compared with Bowie’s solution for both cases and all three d/W, and found to be fairly close. This suggests the element death approach may be employed to simulate crack propagation for approximate prediction in fast high plasticity fractures such as in a collapsing structure subject to impact or blast loadings. As a future work, the present studies can be extended by incorporating the effects of various hole patterns as well as the localized forces transmitted by the bolt(s) to the sheet to achieve a more realistic prediction.